Shifting From SWOT to SWOC: A Combination of Strategic Planning Theory and Financial Strategy Approaches for Organizational Sustainability Performance - Indrasari, Meithiana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Plan strategies to manage the organization, ideally using strategic steps in an integrative and holistic approach. Conditions that force the entire organization/company to be able to adapt to influences both from within and from outside, create their patterns in planning strategies to ensure the sustainability of the business process of the organization/company. In this discussion provides an integrated form of strategic planning using the approach of issue management, strategy management and talent management. The issue as an initial trigger for the upheaval is the basis of how the strategy steps are determined. Furthermore, the strategic management approach by changing the old paradigm of threats into challenges (shiftng from SWOT to SWOC) is the first step towards sustainability for the organization/company. In the last part, using the talent management approach to bring new talents to face the new normal era.